The Coatings in Manufacturing Engineering - Merklein, Marion; Bach, Friedrich-Wilhelm; Bouzakis, Konstantinos D.; Denkena, Berend; Geiger, Manfred; Toenshoff, H. - K. (Trans Tech Publications, 2010)
Coating technology has made great strides during recent years. The properties of surface layers determine the function and quality of entire components. Thus, it is essential to obtain information concerning the development and functionality of the topmost layers. The beneficial effect of coating technology can be observed in many manufacturing fields, where it solves problems such as wear, corrosion, erosion, electrical contact, etc. Even decoration falls under this headin
Keywords: Aluminium Oxide; Bionic Layer; Coating; Cohesive Damage; Contact Angle (CA); Diamond-Like Carbon (DLC); Finite Element Analysis (FEA); Friction; Hot Stamping; Mechanical Property; Optically Non-Cooperative Surface; Plasma Nitriding; Precision Glass Molding; PtIr; PVD Film; Simulation; Thermal Spraying; Tribology; Ultra-Precision Machining; Wear